PEMANFAATAN PROGRAM PENYEDIA LAYANAN INTERNET KECAMATAN (PLIK) SEBAGAI MEDIA PENDIDIKAN JARAK JAUH - Eha Saleha; Jasrial Jasrial; Yuli Tirta Riandi (Jurnal Administrasi Publik, 2016)
Distance education in Indonesia was opened to reduce the education gap betweenurban and remote areas nor with the purpose PLIK program of the Ministry ofCommunications and Information Technology is to reduce the digital divide betweenurban and rural areas. In line with that distance education provides an opportunity toimprove education are not bound classes by utilizing the internet facility and programPLIK give people the chance to improve skills in the field of information technology,including to improve the quality of public education through affordable Internet accessby the availability of internet cafes in the district level and car PLIK to reach people inremote villages. This research was conducted with descriptive qualitative method byanalyzing the data of Indonesia Open University document and the document PLIK ofthe Ministry of Communications and Information Technology. The results showed thatProgram PLIK that began in 2010 has 5939 internet cafes and internet car but wasstopped since 2014 can be used as a medium by universities such as the OpenUniversity which has 39 regional office (UPBJJ) across Indonesia to reach UT studentsin various parts of the region in the service of online registration and tutorial online aswell as to facilitate the UT students get academic information over the internet frominternet cafes and car PLIK provided at district level throughout Indonesia.